Subjective well-being and time use of brazilian PhD professors - Nunes, Maiana Farias Oliveira; Hutz, Claudio Simon; Pires, Jeferson Gervasio; Oliveira, Cassandra Melo (Paidéia (Ribeirão Preto), 2014)
The university professor suffers high pressure to achieve productivity and performs under work conditions that are not always satisfactory. This study seeks to analyze the subjective well-being, the time-use strategies, and the satisfaction with their use of time of PhD-holding professors with and without productivity grants from the National Council for Scientific and Technological Development (CNPq). A total of 83 professors participated in the study (48 with productivity grants), with an average age of 50 years. A total of 89% of participants were from public institutions. The majority of the participants exhibited high levels of negative affect and low-average levels of satisfaction with their use of time. There was no difference in the subjective well-being or in the satisfaction with the use of time when comparing professors who had received a CNPq grant with professors who had not received a CNPq grant. The most important reason for dissatisfaction with the use of time was an excess of work, whereas peer recognition was the primary achievement obtained with the work. How work demands and conditions influence the well-being of the professors is discussed in this study.